2017
DOI: 10.3892/etm.2017.4037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of etomidate on the oxidative stress response and levels of inflammatory factors from ischemia-reperfusion injury after tibial fracture surgery

Abstract: The effect of etomidate on the oxidative stress response and levels of inflammatory factors resulting from ischemia-reperfusion injury of the lower extremities during tibial fracture surgery were investigated. From December 2013 to June 2015, 60 tibial fracture patients with surgical indications for open reduction and internal fixation were selected. Patients were randomly divided into the observation group and the control group. All patients were stanched by tourniquet hemostasis. Patients in the observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…One study in emergency orthopedic surgery ( n = 60), reported a significant reduction of the mean peak IL-6 in patients given TIVA using etomidate versus TIVA with propofol (3240 pg/mL versus 9000 pg/mL, P = .001) [27] . It should be noted that etomidate inhibits the conversion of 11-deoxycortisol to cortisol resulting in transient HPA axis suppression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in emergency orthopedic surgery ( n = 60), reported a significant reduction of the mean peak IL-6 in patients given TIVA using etomidate versus TIVA with propofol (3240 pg/mL versus 9000 pg/mL, P = .001) [27] . It should be noted that etomidate inhibits the conversion of 11-deoxycortisol to cortisol resulting in transient HPA axis suppression.…”
Section: Resultsmentioning
confidence: 99%
“… CRP 24 h TIVA + DEX group, 24 h, CRP = 150 mg/L TIVA group, 24 h, CRP = 120 mg/L No significant difference between groups. [27] China Tibial fracture surgery. Moderate 60 Control group = patients received propofol with remifentanil.…”
Section: Resultsmentioning
confidence: 99%
“… 24 Some studies have shown that ETO pre-treatment can reduce the expression of Bax protein during LILIR in rats, mediating a protective effect. 17 ETO may play a protective role in reperfusion injury by activating gamma-aminobutyric acid receptors, increasing the permeability of the cell membrane to Cl ions and preventing depolarization the cell membrane. 25 In addition, the N-methyl-D-aspartate receptor and the Ca 2+ -channel are voltage dependent; inhibition of cell membrane depolarization leads to decreased Ca 2+ influx and decreased cellular oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Fas and its ligand FasL have been thoroughly studied with a profound impact on our understanding of the mechanisms of apoptosis. [17][18][19] CsA is a cyclic peptide comprising 11 amino acids. It is an active metabolite of fungi in soil and has strong immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines (e.g. TNF-alpha, IL-1 and IL-6) typically reach peak values after fracture operations [5], and it is suggested that these proinflammatory reactions may critically influence the process of bone regeneration.…”
Section: Introductionmentioning
confidence: 99%